MENCIPTAKAN BUDAYA BELAJAR EFEKTIF DALAM MENINGKATKAN MUTU PENDIDIKAN (Studi Kasus Di MI Bustanul Ulum Brudu Jombang) - Arif, Moh. (Al Tadib : Jurnal Ilmu Pendidikan, 2015)
This study aims to discuss how the process ofcreating an effective learning culture in MI BustanulUlum Brudu in improving the quality of education thatis always associated with the process of teaching andlearning activities with the goal of achieving quality andthe quality of education in madrasas. The quality ofeducation has been achieved because of the awarenessand participation of all elements of education in MIBustanul Ulum, so it can form an effective teaching andlearning culture. For that, universally takes appropriatemeasures by way of intertwining komonikasi, theparticipation of all the elements of education, qualifiedhuman resources, planning and intensive guidance. Allthis can be carried out continuously either at the schoolor outside the madrasah.Keywords: cultural effective learning and improving the